Targeting nail psoriasis: IL-17A inhibitors demonstrate site-specific superiority over IL-23 inhibitor in a 24-week dermoscopy-guided real-world cohort - Yan, Xiamei; Shi, Minglan; Wang, Bin; Zeng, Lihua; Wang, Huiwei; Shi, Jialiang; Cui, Yaqian; Hou, Suchun (Frontiers in Immunology, 2025)
ObjectiveTo compare the real-world clinical efficacy and safety of interleukin (IL)-17A inhibitors (secukinumab [SEC] and ixekizumab [IXE]) versus the IL-23 inhibitor guselkumab (GUS) in patients with nail psoriasis, with a focus on site-specific biologic therapeutic responses (nail matrix vs. nail bed) in a 24-week prospective observational cohort.MethodsThis cohort enrolled 65 adult patients with plaque psoriasis and dermoscopy-confirmed nail involvement, stratified into three treatment groups: SEC (n=25), IXE (n=20), and GUS (n=20). Outcome assessments at baseline and week 24 included: Nail Psoriasis Severity Index (NAPSI) with domain-specific scoring (matrix/bed) by dermoscopic evaluation using a 10× polarized handheld device; Psoriasis Area and Severity Index (PASI), Body Surface Area (BSA); Dermatology Life Quality Index (DLQI). Safety was monitored through treatment-emergent adverse events (TEAEs).Results(1) By week 24, PASI, BSA, DLQI and NAPSI scores had significantly decreased from baseline in all groups (P<0.001). (2) By week 24: SEC, IXE, and GUS groups saw nail matrix NAPSI score improvements of 65.9%, 60.5%, and 51.5%, with 68%, 55%, and 30% achieving NAPSI 60; Nail bed NAPSI score improvements were 58.8%, 68.6%, and 65.8%, with 28%, 65%, and 40% achieving NAPSI 60; Total NAPSI score improvements were 62.7%, 64.6%, and 53.7%, with 44%, 70%, and 30% achieving NAPSI 60. (3) All patients in the SEC and IXE groups achieved PASI 75, compared to 85% in the GUS group. SEC showed PASI 90 and PASI 100 response rates of 80% and 36%, while IXE of 60% and 30%. (4) TEAEs were mild, including: injection site reactions: 15% (IXE group); eczematous rashes: 8% (SEC group). No TEAEs were reported in the GUS group, and no serious adverse events occurred in any group.ConclusionIL-17A inhibitors and the IL-23 inhibitor demonstrated significant efficacy in improving both nail and skin lesions in psoriasis. Notably, IL-17A inhibitors exhibited superior overall efficacy compared to IL-23 inhibitor. Specifically, SEC excelled in improving dermoscopic nail matrix changes, whereas IXE was more potent for nail bed pathology. All groups significantly improved patients’ life quality and exhibited good safety profiles.